Pengaruh Komunikasi dan Budaya Organisasi Terhadap Efektivitas Kinerja Pegawai Dinas Pertanian Provinsi Banten - Muhammad Arifin Ilham; Mira Nurhikmat; Didi Wandi (Universitas 45 Surabaya, 2025)
This research aims to determine the influence of communication and organizational culture on performance effectiveness. This research uses quantitative research as research objects at the Banten Province Agricultural Service with a population of 182 and 64 respondents. Sampling uses random sampling. This research data was taken using a questionnaire. The analysis technique used was validity, reliability, multiple linear tests, T tests and F tests using the SPSS version 27 application. The results of the analysis concluded that the Communication Variable (X1) had a positive and significant effect on Employee Performance Effectiveness (Y). The Organizational Culture variable (X2) has a positive and significant effect on Employee Performance Effectiveness (Y). The variables Communication (X1) and Organizational Culture (X2) simultaneously have a positive and significant effect on the Effectiveness of the Performance of Banten Province Agricultural Service Employees.